The role of congruence between exploitative and exploratory knowledge sharing in enterprise systems project: polynomial modeling and response surface analysis - Liu, Yang; Cai, Zhao; Liu, Hefu (Association for Information Systems, 2018)
In enterprise system (ES) project, knowledge sharing between client and ES vendor is a pivotal practice to ensure its success. However, it is a tradeoff for managers to balance two forms of knowledge sharing – exploitative and exploratory knowledge sharing. This study provides a preliminary insight by investigating the effects of congruence and incongruence of knowledge sharing on the success of ES project. Using data collected from 112 clients of an ES vendor, we apply polynomial modeling and response surface methodology for an in depth analysis. Our findings point out the importance of congruence between the two forms of knowledge sharing and we also find that exploratory knowledge sharing between client and ES vendor is a prerequisite to the success of ES project. In future research, we aim to examine how to balance the two forms of knowledge sharing and find out which kind of knowledge should be necessarily shared.